Comparison of MAS-PCR and GenoType MTBDR assay for the detection of rifampicin-resistant Mycobacterium tuberculosis. - Tho, D; Ha, D; Duy, P; Lan, N; Hoa, D; Chau, N; Farrar, J; Caws, M (2008)
SETTING: Pham Ngoc Thach Hospital for Tuberculosis and Lung Diseases, the tertiary referral hospital for tuberculosis (TB) in Southern Vietnam. OBJECTIVE: To develop and evaluate a simple, rapid and accurate multiplex allele specific polymerase chain reaction (MAS-PCR) test to detect rifampicin (RMP) resistance point mutations at codons 516, 526 or 531 in the rpoB gene of Mycobacterium tuberculosis. DESIGN: The novel MAS-PCR was compared with the commercial M. tuberculosis Drug Resistance (MTBDR) test in 104 RMP-resistant and 50 RMP-susceptible routine isolates, defined by conventional 1% phenotypic susceptibility testing. RESULTS: The sensitivity of the MAS-PCR and MTBDR tests was respectively 83.7% (95%CI 75.1-90.2) and 93.3% (95%CI 86.6-97.3). Both tests were 100% specific. The negative predictive value was 74.6% (95%CI 65.3-83.1) for the MAS-PCR and 87.7% (95%CI 80.0-93.6) for the MTBDR test. CONCLUSION: The MTBDR test, although more sensitive, is currently prohibitively expensive in resource-poor, high-burden settings. The MAS-PCR described here presents a less laborious economic alternative. A susceptible result returned by either test cannot be used to exclude multidrug-resistant TB.